In Search for the Open Educator: Proposal of a Definition and a Framework to Increase Openness Adoption Among University Educators - Nascimbeni, Fabio; Burgos, Daniel (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2016)
The paper explores the change process that university teachers need to go through in order to become fluent with Open Education approaches. Based on a literature review and a set of interviews with a number of leading experts in the field of Open Educational Resources and Open Education, the paper puts forward an original definition of Open Educator which takes into account all the components of teachers’ work: learning design, teaching resources, pedagogical approaches and assessment methods- of teachers’ activities. Subsequently, to help the development of teachers’ openness capacity, the definition is further developed into a holistic framework for teachers, which takes into account all the dimensions of openness included in the definition and which provides teachers with self-development paths along each dimension. By working on the definition and on the framework with the interviewed experts, the paper concludes that a strong relation exists between the use of open approaches and the networking and collaboration attitude of university teachers, and that in order to overcome the technical and cultural barriers that hinder the use of open approaches in Higher Education, it is important to work on the transition phases – in terms of awareness and of capacity building - that teachers have to go through in their journey towards openness.